2021
DOI: 10.1093/ckj/sfaa161
|View full text |Cite
|
Sign up to set email alerts
|

Speckle-tracking echocardiography in comparison with ejection fraction for prediction of cardiovascular mortality in patients with end-stage renal disease

Abstract: Background Cardiovascular disease is the major cause of death in end-stage renal disease (ESRD). To develop better means to assess cardiovascular risk in these patients, we compared conventional echocardiography-derived left ventricular ejection fraction (EF) with the novel method of 2D speckle-tracking echocardiography to determine cardiac strain. Methods Predictive performances of conventional EF and speckle-tracking echoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…A less negative value is indicative of worse systolic LV function. GLS is a sensitive measure of systolic function and has recently been identified in adult KF as a more precise predictor of cardiovascular mortality than ejection fraction [ 46 ]. Regional strain can be assessed by STE and has been used to help define mechanical dyssynchrony [ 30 ].…”
Section: The Natural History Of Cvd In Pediatric Kidney Failurementioning
confidence: 99%
“…A less negative value is indicative of worse systolic LV function. GLS is a sensitive measure of systolic function and has recently been identified in adult KF as a more precise predictor of cardiovascular mortality than ejection fraction [ 46 ]. Regional strain can be assessed by STE and has been used to help define mechanical dyssynchrony [ 30 ].…”
Section: The Natural History Of Cvd In Pediatric Kidney Failurementioning
confidence: 99%
“…7,8 Currently, echocardiography is a routine method for cardiac measurement, and LVEF has been recommended as an indicator for risk stratification in patients with ESRD. 9 However, LVEF as a predictor of MACE in ESRD patients, has some limitations, including failure to account for differences in left ventricular mass and size, which have been shown to be prognostic in several CVDs, including uremic cardiomyopathy. [10][11][12] Moreover, early cardiac impairment in patients with ESRD is manifested as diastolic dysfunction with preserved ejection fraction, and LVEF does not reflect this early cardiac impairment.…”
mentioning
confidence: 99%
“… 3 Despite this limitation GLS was proven to be an important predictor of cardiovascular (CV) events in hemodialysis patients. 4 …”
mentioning
confidence: 99%
“…3 Despite this limitation GLS was proven to be an important predictor of cardiovascular (CV) events in hemodialysis patients. 4 The importance of GLS in arterial hypertension is well established and it has been even involved in the guidelines for imaging in hypertensive patients. 5 It was also demonstrated that GLS has a significant predictive value, that was higher of LVEF for prediction of CV events.…”
mentioning
confidence: 99%
See 1 more Smart Citation